Heat Conduction Modeling of Fiber Fuse in Single-Mode Optical Fibers. (24th February 2014) - Shuto, Yoshito
Abstract : The unsteady-state thermal conduction process in single-mode optical fiber was studied theoretically with the explicit finite-difference method. We assumed that the vitreous silica optical fiber underwent pyrolysis at elevated temperatures to formSiO x (x 1 ). We also proposed a model in which the optical absorption coefficient of the core layer increased with increasing molar concentration ofSiO x . The core-center temperature changed suddenly and reached over3 × 10 4 K when a 1.064- μ m laser power of 2 W was input into a short core layer of 40 μ m length, which was heated at 2923 K. This thermal wave, that is, a fiber fuse, increased in size and propagated toward the light source at a rate of about 0.54 m/s. The calculated propagation velocity of the fiber fuse was in agreement with the experimental value. Moreover, the average temperature of the radiated region of the core layer gradually approached a temperature of about 5700 K. It was found that the final average temperature was close to the experimentally reported values.